Your mother was a Neanderthal - Scieszka, Jon (Scieszka, Jon. Time warp trio, 1993)
The Time Warp Trio find themselves in the middle of an adventure in prehistoric times, where cave art is a form of graffiti and "rock" music takes on a whole new meaning.